ANALYSIS OF JUDGE'S DECISION ON AKAD MURABAHAH TORT CASE IN RELIGIOUS COURT - Azhar Alam; Aditya Nurrahman; Raisa Aribatul Hamidah (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThe Religious Courts currently handle Sharia economic cases. One of the cases that dominates sharia financial matters is the default on the Murabaha Agreement. This study aims to determine the basic considerations of Klaten Religious Court judges in resolving Sharia economic cases in Murabaha contracts. This research also tries to test whether decisions in deciding patients fulfill the principles of justice. This research is field research with a normative juridical approach. Religious Court data was collected through interviews and documentation in religious courts. This study shows the legal sources of the two cases studied using draft law sources - the Civil Code (KUHPerdata) and Article 181 HIR. This research also reveals that the judge's conclusion was based on procedural law, applicable rules and regulations, and party benefits. This study suggests that disputing parties should be more careful in preparing materials for religious court cases to achieve the expected results.Keywords: Justice; Legal Considerations; Murabaha; Judgment of the Court.